(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The study aimed to identify the contribution of digital transformation and cloud computing in enhancing the accounting profession. The descriptive analytical approach was used to achieve the study objectives and a questionnaire was used to collect data from the study community, which consisted of academics and experts in the field of accounting in the city of Sirte, Libya. The study distributed 60 questionnaires to the targeted sample and found several results, the most important of which is that there is a significant and meaningful contribution of both digital transformation and cloud computing in enhancing the accounting profession. The study recommended several recommendations, including the need to follow the mechanisms of digital transformation and cloud computing in accounting work and the necessity of providing a suitable environment for the use of digital transformation and cloud computing in accounting.